2020
DOI: 10.56093/ijans.v90i1.98217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of Lactobacillus acidophilus on blood biochemical profile, antioxidant activity and plasma immunoglobulin level in neonatal Murrah buffalo calves

Abstract: An experiment was designed to evaluate the effect of dietary supplementation of Lactobacillus acidophilus on blood biochemical profile, antioxidant activity and plasma immunoglobulin level in neonatal Murrah buffalo calves. The 90 day trial was conducted on 24 neonatal Murrah buffalo calves randomly divided into 4 dietary treatments, viz. CON (basal diet alone), T1 (basal diet + L. acidophilus as a fermented milk @ 100 mL/calf/day having 108 CFU/mL), T2 (basal diet + L. acidophilus as a fermented milk @ 200 mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…Probiotics have the ability to influence signalling pathways, including NF-κB, MAPK, Nrf-2, and SIRTs, at the molecular level, hence producing antioxidant benefits 73 , 74 . Similar to the current investigation, Ojha et al 15 found that supplementation with Lactobacillus acidophilus improved superoxide dismutase (SOD) activity, while maintaining catalase and glutathione peroxidase (GPx) activity in all groups. Likewise, Wang et al 75 reported that feeding microencapsulated probiotics and prebiotics significantly increased the total antioxidant capacity in the broiler chickens.…”
Section: Resultssupporting
confidence: 85%
“…Probiotics have the ability to influence signalling pathways, including NF-κB, MAPK, Nrf-2, and SIRTs, at the molecular level, hence producing antioxidant benefits 73 , 74 . Similar to the current investigation, Ojha et al 15 found that supplementation with Lactobacillus acidophilus improved superoxide dismutase (SOD) activity, while maintaining catalase and glutathione peroxidase (GPx) activity in all groups. Likewise, Wang et al 75 reported that feeding microencapsulated probiotics and prebiotics significantly increased the total antioxidant capacity in the broiler chickens.…”
Section: Resultssupporting
confidence: 85%
“…In both the C and T groups, total serum protein, albumin, globulin, A:G ratio, and glucose levels were within the physiological range. These findings align with Chaudhary et al, (2008) [2] and Ojha et al, (2020) [8] , who reported comparable concentrations in control animals and those supplemented with probiotics. Frizzo et al, (2008) [3] observed similar results after supplementing probiotics in Holstein calves, where globulin significantly increased, indicating enhanced immunity.…”
Section: Serum Biochemical Parameterssupporting
confidence: 91%
“…Kutluyer et al, (2017) found that the level of SOD was not influenced by potassium humate and probiotic supplementation, while the level of GPx (p>0.05) was reduced by supplementation in brown Swiss calves. In a study by Ojha et al, (2020) [8] , an increase in total antioxidant (TA) activity was observed in T 2 (L. acidophilus fermented milk at 200 mL/calf/day with 10 8 CFU/ml) and T 3 (L. acidophilus fermented milk at 300 ml/calf/day with 10 8 CFU/mL) compared to the control, with an intermediate level in T 1 (L. acidophilus fermented milk at 100 mL/calf/day with 10 8 CFU/mL). The activity of SOD was significantly higher in the T 1 , T 2 , and T 3 groups compared to the control, while the activities of catalase and glutathione peroxidase (GPx) remained consistent across all groups during the experimental period.…”
Section: Erythrocytic Antioxidant Profilementioning
confidence: 96%